2013
DOI: 10.1161/jaha.112.000075
|View full text |Cite
|
Sign up to set email alerts
|

Daily Ischemic Preconditioning Provides Sustained Protection From Ischemia–Reperfusion Induced Endothelial Dysfunction: A Human Study

Abstract: BackgroundIt is well established that acute ischemic preconditioning (IPC) protects against ischemia–reperfusion (IR) injury; however, the effectiveness of repeated IPC exposure has not been extensively investigated. We aimed to determine whether daily IPC episodes provide continued protection from IR injury in a human forearm model, and the role of cyclooxygenase‐2 in these responses.Methods and ResultsThirty healthy volunteers were randomized to participate in 2 of 3 protocols (IR alone, 1‐day IPC, 7‐day IPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 42 publications
3
37
0
4
Order By: Relevance
“…One recent study repeated IPC over nine consecutive days but failed to see any improvement in aerobic capacity. 7 Repeated IPC has been investigated in clinical studies, with local and remote improvements in endothelial function, brachial artery flowmediated dilation and resting skin microcirculation being observed, [8][9][10] although the physiological basis of this 'hyperconditioning' is still to be fully elucidated. 11 Oxidative stress is an integral component of ischaemia/reperfusion, 12 while vasodilation improved tissue oxygenation, 13 14 and inflammatory system modulation 15 is regulated through single or repetitive ischaemic treatment.…”
Section: Background/aimmentioning
confidence: 99%
“…One recent study repeated IPC over nine consecutive days but failed to see any improvement in aerobic capacity. 7 Repeated IPC has been investigated in clinical studies, with local and remote improvements in endothelial function, brachial artery flowmediated dilation and resting skin microcirculation being observed, [8][9][10] although the physiological basis of this 'hyperconditioning' is still to be fully elucidated. 11 Oxidative stress is an integral component of ischaemia/reperfusion, 12 while vasodilation improved tissue oxygenation, 13 14 and inflammatory system modulation 15 is regulated through single or repetitive ischaemic treatment.…”
Section: Background/aimmentioning
confidence: 99%
“…They provided evidence that repeated RIPC enhanced resistance artery endothelial function via increases in nitric oxide production, whereas daily repeated RIPC augmented both circulating endothelial progenitor cells and plasma concentrations of vascular endothelial growth factor. Luca et al (2013) followed this work by exploring whether repeated (daily) IPC alters the efficacy of a single IPC against endothelial ischaemia-reperfusion injury. They also found that 7 days of daily IPC provided sustained protection against ischaemia-reperfusion injury of the endothelium of peripheral arteries.…”
Section: What Are the Cardiovascular Adaptations To Repeated Ipc?mentioning
confidence: 99%
“…1,2 Recent studies have examined daily exposure of IPC episodes as a therapeutic intervention and found enhanced brachial artery endothelial function 3 , skin perfusion 3 , resistance 4 artery function and protection from conduit artery induced IRI 5 . Therefore, daily IPC may potentially be a useful intervention to improve vascular function.…”
Section: Introductionmentioning
confidence: 99%